Structure-Dependent Inhibition of Stenotrophomonas maltophilia by Polyphenol and Its Impact on Cell Membrane - Zhang, Yuxiang; Wei, Jianping; Qiu, Yue; Niu, Chen; Song, Zihan; Yuan, Yahong; Yue, Tianli (Frontiers in Microbiology, 2019)
As natural occurring antimicrobial substances, phenolic compounds have been used to inhibit various bacteria. Stenotrophomonas maltophilia 4–1, a strain isolated from food, exhibited spoilage potential in vitro with proteolysis and lipolysis at 25°C. The present study evaluated the antibacterial properties of 13 polyphenols on S. maltophilia 4–1, and selected 6 compounds (ferulic acid, p-coumaric acid, caffeic acid, chlorogenic acid, (-)-epigallocatechin, and phloretin) for binary combination treatments. The results revealed that antibacterial activities of polyphenols were structure-dependent, and cinnamic acid showed strong inhibitory effects, with a minimum inhibitory concentration (MIC) of 0.125 mg/mL. Importantly, we did not observe any obvious synergistic effects across all binary combinations. The antibacterial mechanism of cinnamic acid was related to membrane damage, caused by the loss of cell membrane integrity and alteration of cell morphology. These findings suggest that cinnamic acid is a promising candidate for the control of spoilage bacteria in food.